2D Transition Metal Oxides/Hydroxides for Energy‐Storage Applications. Issue 7 (23rd December 2015) - Tan, Hui Teng; Sun, Wenping; Wang, Libo; Yan, Qingyu
Abstract: The development of 2‐dimensional materials has expanded beyond the realm of graphene, and now includes inorganic 2‐dimensional transition metal oxides/hydroxides, which show promise for a wide range of applications. As an emerging class of nanoscale materials, they show unprecedented properties that are unattainable in their bulk lamellar systems, which can be attributed to their confined thickness compared to several tens of micrometer lateral dimensions. Such qualities make them viable candidates for battery and supercapacitor applications. There are a few challenges ahead for 2‐dimensional transition metal oxides/hydroxides, including the limited types of 2‐dimensional parent materials in bulk form, the controlled synthesis of 2‐dimensional nanostructures with nonlayered structures, and the ability to control the properties of layers by tuning the chemistry and nanoscopic features. This Focus Review will cover the research landscape of 2‐dimensional transition metal oxides/hydroxides, ranging from synthetic approaches, to understanding the properties that emerge at the single‐layer scale, to exploiting these properties in both new and existing technologies. Abstract : Inorganic 2D metal oxides/hydroxides with confined thickness and lateral dimensions in the range of several tens of micrometers serve as a fertile ground for a wide range of applications, particularly batteries and supercapacitors.